Immediate hypersensitivity reactions to steroids and steroid containing medications. Issue 4 (August 2020) - Rutkowski, Krzysztof; Wagner, Annette; Rutkowski, Ryszard
Abstract : Purpose of review: Although rare and counterintuitive, hypersensitivity reactions to corticosteroids have been reported since the 1950s. Delayed hypersensitivity reactions following cutaneous exposure (contact allergy) are well understood and principles of testing, as well as cross-reactivity patterns, have been established. In contrast, understanding of immediate hypersensitivity reactions and delayed hypersensitivity reactions after systemic exposure is evolving more slowly. However, progress has been made in the delineating of underlying pathogenic mechanisms and in the development of testing. Recent findings: IgE-mediated hypersensitivity reactions to corticosteroids have been described. It has been recognized that some, if not all of them, may be due to excipients in steroid formulations. Two excipients, polyethylene glycol and carboxymethylcellulose, seem of particular importance, but cases of reactions to polysorbate 80 and lactose have also been reported. The use of skin testing but also, increasingly, in-vitro methods such as basophil activation test is improving diagnostic accuracy. Summary: The recognition of the role of excipients is leading to a paradigm shift in our approach to immediate hypersensitivity to corticosteroids. Improved access to in-vivo and in-vitro testing will enhance our understanding of true corticosteroid immediate allergy.